Complete genome sequence and probiotic properties of Lactococcus petauri LZys1 isolated from healthy human gut. Issue 8 (16th August 2021) - Li, Ouyang; Zhang, Huijian; Wang, Wenjing; Liang, Yuxin; Chen, Wenbi; Din, Ahmad Ud; Li, Li; Zhou, Yingshun
Abstract : Introduction. Lactococcus petauri LZys1 ( L. petauri LZys1) is a type of lactic acid bacteria (LAB), which was initially isolated from healthy human gut. Hypothesis/Gap Statement. It was previously anticipated that L. petauri LZys1 has potential characteristics of probiotic properties. The genetic structure and the regulation functions of L. petauri LZys1 need to be better revealed. Aim. The aim of this study was to detect the probiotic properties L. petauri LZys1 and to reveal the genome information related to its genetic adaptation and probiotic profiles. Methodology. Multiple in vitro experiments were carried out to evaluate its lactic acid-producing ability, resistance to pathogenic bacterial strains, auto-aggregation and co-aggregation ability, and so on. Additionally, complete genome sequencing, gene annotation, and probiotic associated gene analysis were performed. Results. The complete genome of L. petauri LZys1 comprised of 1 985 765 bp, with a DNA G+C content of 38.07 %, containing 50 tRNA, seven rRNA, and four sRNA. A total of 1931 genes were classified into six functional categories by Kyoto Encyclopaedia of Genes and Genomes (KEGG) database. The neighbour-joining phylogeny tree based on the whole genome of L. petauri LZys1 and other probiotics demonstrated that L. petauri LZys1 has a significant similarity to Lactococcus garvieae . The functional genes were detected to expound the molecular mechanism and biochemical processes of its potential probiotic properties, such as atpB gene. Conclusion. All the results described in this study, together with relevant information previously reported, made L. prtauri LZys1 a very interesting potential strain to be considered as a prominent candidate for probiotic use.